An integrated methodological framework for the validation and verification of clinical testing by qRT-PCR - Carolina Cardona-Ramírez; Cruz Elena Enríquez-Valencia; Gina Méndez-Callejas; Giovanna Meza Barreto; Gabriel Andrés Tafur-Gómez; Danny Wilson Sanjuanelo-Corredor (Heliyon)
This paper outlines a practical method for validating quantitative-qualitative techniques used to detect genetic material through qRT-PCR, specifically focusing on SARS-CoV-2 testing and adhering to ISO/IEC 17025:2018 accreditation standards. Despite the prevalence of quantitative-qualitative screening in genetic testing, comprehensive validation guidelines remain a notable gap in the field. Such guidelines could be applied to other molecular testing areas that rely on these techniques, particularly those involving sample handling, automated extraction, and amplification processes, which can significantly impact results. This work describes the statistical approaches behind qRT-PCR protocols, followed by a technical characterization profile of the validation process. Modifications to the gold standard method allowed us to establish a technical limit of detection (LOD) of 5,09 copies/reaction at a 95 % confidence interval.